2022
DOI: 10.2341/20-301-c
|View full text |Cite
|
Sign up to set email alerts
|

36-Month Randomized Clinical Trial Evaluation of Preheated and Room Temperature Resin Composite

Abstract: SUMMARY Objective: This study evaluated the effect of preheating resin composites (RCs) on the clinical performance of class I restorations during a 36-month period using a split-mouth, double-blinded randomized design. Methods and Materials: A total of 35 patients were selected. Every patient received one pair of class I nanofilled resin composite (RC, Filtek Z350 XT) posterior restorations (n=70). One side of the mouth received preheated composites; on the other side, the compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
7
11
0
Order By: Relevance
“…This seems to be an advantage when preheating was used, mainly because the increase of the flowability of composite when preheating improves the marginal adaptation of the cavity. These findings align with those by Elkaffas et al [27], who found that the difference between preheating and nonpreheating composite resin restorations performed in posterior restorations were non-significant, even after 36 months of clinical evaluation. However, in the mentioned study, only 3% of the restorations showed marginal defects [27].…”
Section: Favoreto Mw Et Alsupporting
confidence: 91%
See 4 more Smart Citations
“…This seems to be an advantage when preheating was used, mainly because the increase of the flowability of composite when preheating improves the marginal adaptation of the cavity. These findings align with those by Elkaffas et al [27], who found that the difference between preheating and nonpreheating composite resin restorations performed in posterior restorations were non-significant, even after 36 months of clinical evaluation. However, in the mentioned study, only 3% of the restorations showed marginal defects [27].…”
Section: Favoreto Mw Et Alsupporting
confidence: 91%
“…These findings align with those by Elkaffas et al [27], who found that the difference between preheating and nonpreheating composite resin restorations performed in posterior restorations were non-significant, even after 36 months of clinical evaluation. However, in the mentioned study, only 3% of the restorations showed marginal defects [27]. Several methodological differences (including cavity type and composite resin used) between the present study and the previous one help explain these differences.…”
Section: Favoreto Mw Et Alsupporting
confidence: 91%
See 3 more Smart Citations